2010
DOI: 10.1590/s1677-04202010000100002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidative and proteolytic activities and protein profile of laticifer cells of Cryptostegia grandiflora, Plumeria rubra and Euphorbia tirucalli

Abstract: In this study, proteins extracted from laticifer cells of three plants were examined by electrophoresis, mass spectrometry (MALDI-TOF) and characterized in respect of proteolytic, chitinolytic and anti-oxidative activities by means of zymography and colorimetric assays. Acidic proteins with molecular masses between 12.5 and 74.5 kDa predominated in laticifers of P. rubra. This profile was not found in laticifers of C. grandiflora and E. tirucalli. The later was poor in respect of proteins. Strong anti-oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
4
29
0
1
Order By: Relevance
“…Furthermore, latex generated deleterious effects in insects may be due to presence of α-amylase inhibitors [53], N-acetyl-β-d-glucosaminase [54], flavonoids [55] and different types of lectins [56]. As it is already reported that laticifer fluids from Calatropis procera contain endogenous soluble proteins which are enzymatic in nature [57] and show proteolytic [49,58] and insecticidal activity [49], these proteins mainly proteases found in different plant latexes [46,59] seem to be associated with insecticidal activity [60,57] and play a defensive role in plants [61] similar to lectin molecules [56]. C. procera latex also contains Kunitz-type trypsin inhibitors [62] which inhibit feeding in caterpillars by disrupting peritrophic matrix [63].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, latex generated deleterious effects in insects may be due to presence of α-amylase inhibitors [53], N-acetyl-β-d-glucosaminase [54], flavonoids [55] and different types of lectins [56]. As it is already reported that laticifer fluids from Calatropis procera contain endogenous soluble proteins which are enzymatic in nature [57] and show proteolytic [49,58] and insecticidal activity [49], these proteins mainly proteases found in different plant latexes [46,59] seem to be associated with insecticidal activity [60,57] and play a defensive role in plants [61] similar to lectin molecules [56]. C. procera latex also contains Kunitz-type trypsin inhibitors [62] which inhibit feeding in caterpillars by disrupting peritrophic matrix [63].…”
Section: Discussionmentioning
confidence: 99%
“…The plant has been investigated for antibacterial (Hamburger et al, 1991;Egwaikhide et al, 2007Egwaikhide et al, , 2009Kuigoua et al, 2010;Baghel et al, 2010;Dey et al, 2011), antifungal (Kuigoua et al, 2010;Souza et al, 2011;Gaitan et al, 2011), antimicrobial (Mahady, 2002), antialgal (Kuigoua et al, 2010), larvicidal (Ramos et al, 2009;Patil et al, 2012), molluscicidal (Hamburger et al, 1991), piscicidal (Joshi and Joshi, 2006), nematicidal (Joymati, 2010), antioxidative and free radical scavenging activities (Ruiz-Teran et al, 2008), hypolipidemic (Merina et al, 2010), proteolytic (De Freitas et al, 2010), cytotoxic (Kardono et al, 1990;Hamburger et al, 1991;Rekha and Jayakar, 2011), abortifacient (Dabhadkar and Zade, 2012) and anti HIV (Tan et al, 1991) properties. The biocatalytic activity in terms of lipase activity in hydrolysis and acyl transfer reactions of latex was compared with that of babaco (Vasconcellea x Heilbornii Cv.)…”
Section: Pharmacologymentioning
confidence: 99%
“…It is important to cite that laticiferous proteins from C. procera have been shown to be deleterious to some crop pests but not to other (Ramos et al, , 2010. Furthermore we have recently demonstrated that both C. procera and P. rubra laticifer proteins are highly detrimental to both insects tested here when added in artificial diets (to appear elsewhere).…”
Section: Discussionmentioning
confidence: 61%
“…The procedure to isolate the whole laticifer proteins has been published in several of our own works and checked by electrophoresis. For more information and details of the methodology see Freitas et al (2007Freitas et al ( , 2010. The other two fractions are merely the complementary material of the fractionated latices obtained by precipitation or exclusion by dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation